Peranan Harga Diri sebagai Variabel Moderasi dalam Hubungan antara Depresi dan Keberfungsian Sosial Internal Remaja - Husmiati Husmiati (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
The main purpose of this study is to examine the significant influence of self dignity as moderating vairable in the relationship between depression and youth’s inner social functioning. A total of 121 youths dropout from school who received social rehabilitation program at Panti Sosial Bina Remaja (PSBR) in Cimahi, Indonesia, in 2012, were selected as respondentsthrough purposive technique. Research instrument was modified from standardized intrument such as: youth depression scale was modified from the generalized contentment scale; Youth self-esteem scale was modified from the Rosenberg Self Esteem Scal; and the inner social functioning scale was modified from inner-interaction social functioning scale. The results of this study found that the youths’ self-esteem was a significant role as moderating variable in relationship between youth depression and their inner social functioning. Therefore, the youths’ self-dignity factor is very important in addressing the youth problems especially depression that can be improved as their inner social functioning.